2015
DOI: 10.2139/ssrn.2567433
|View full text |Cite
|
Sign up to set email alerts
|

News Sentiment to Market Impact and its Feedback Effect

Abstract: Although market feedback on investor sentiment effect has been conceptually identified in the existing finance literature, and investment strategies have been designed to explore this effect, there lacks systematic analysis in a quantified manner on such effect. Digitization of news articles and the advancement of computational intelligence applications have led to a growing influence of news sentiment over financial markets in recent years. News sentiment has often been used as a proxy for gauging investor se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…As Zullow's ground-breaking research indicates, a large number of studies in economics and related fields show that there is a more general relationship between economic conditions and public sentiment. More recent exemplars of this have used digital resources to investigate corpus-level or massive sets of data, such as those obtained from blogs and social media posts (e.g., Gruhl et al, 2005;Ranco et al, 2015), books (e.g., Bentley et al, 2014), and public news articles (e.g., Chan, 2003;Shapiro et al, 2020;Mo et al, 2016). For instance, Bollen et al (2011) examined whether public mood states could predict changes in the stock market by analysing the overall valence and a range of moods expressed within a large corpus of social media posts, showing that changes in the combined calm and happiness mood dimensions were predictive of changes in the Dow Jones Industrial Average values with a three-day lead (Bollen et al, 2011).…”
Section: Lyrical Themes and Socioeconomic Conditionsmentioning
confidence: 99%
“…As Zullow's ground-breaking research indicates, a large number of studies in economics and related fields show that there is a more general relationship between economic conditions and public sentiment. More recent exemplars of this have used digital resources to investigate corpus-level or massive sets of data, such as those obtained from blogs and social media posts (e.g., Gruhl et al, 2005;Ranco et al, 2015), books (e.g., Bentley et al, 2014), and public news articles (e.g., Chan, 2003;Shapiro et al, 2020;Mo et al, 2016). For instance, Bollen et al (2011) examined whether public mood states could predict changes in the stock market by analysing the overall valence and a range of moods expressed within a large corpus of social media posts, showing that changes in the combined calm and happiness mood dimensions were predictive of changes in the Dow Jones Industrial Average values with a three-day lead (Bollen et al, 2011).…”
Section: Lyrical Themes and Socioeconomic Conditionsmentioning
confidence: 99%
“…Using a theoretical framework, Arnold and Brunner (2015) showed that positive feedback trading causes price overreaction and the impacts of feedback trading would be dampened if news is incorporated into price in time. Mo et al (2016) analyzed more than 12 million news articles and documented the presence of a significant feedback effect between news sentiment and market returns across the major indices in the US financial market.…”
Section: Investor Sentiment and Market Return Literaturementioning
confidence: 99%
“…Shleifer (2000) argued that investor sentiment is the cause of numerous market anomalies such as noise trader risk, limits of arbitrage, and closed-end fund puzzle. This claim has been echoed by a number of empirical studies showing predictive power of investor sentiment to financial market prices (Antweiler and Frank 2004, Tetlock 2007, Tetlock et al 2008, Mo et al 2016. On the other hand, other studies showed market price movements affect investor sentiment such as Antoniou et al (2005), Salm and Schuppli (2010), and Arnold and Brunner (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their work analyzes sentiment at the topic level and not at the sentence level as in [15,25]. Other recent works in the literature that perform sentiment analysis include [16,17,19,28,32]. These works utilize sentiment dictionaries and extract sentiments from text and predict stock price movements or market returns.…”
Section: Related Literaturementioning
confidence: 99%